Detecting Shallow Water Submarine Cables with Single Beam Echosounder in Tidung Island - M Hasbi Sidqi Alajuri; Henry M. Manik; Muhammad Zainuddin Lubis; RozeffPramana; Basyaruddin Islmail Harahap; Doli Bonardo; Marisha Pertiwi; Suhengki (Journal of Applied Geospatial Information, 2026)
Detecting submarine cables in tropical shallow waters remains challenging due to environmental complexity and the similarity of backscatter signatures to other seafloor objects. This study characterizes the acoustic backscatter response of two types of submarine cables concrete-armored and non-armored in the waters of Tidung Island using a SIMRAD EK-15 and a Furuno FCV-628 echosounder operating at 200 kHz. Data processing was conducted to derive Volume Backscattering Strength (SVc) and Surface Scattering Strength (SS). Measurements of the concrete-armored cable using the Furuno system produced SVc values of −6.701 dB and −5.055 dB, and SS values of −11.855 dB and −9.510 dB, indicating high reflectivity due to the impedance contrast between concrete and seawater. In contrast, measurements of the non-armored cable using the SIMRAD system yielded SVc values of −11.547 dB and −12.600 dB and SS values of −14.612 dB and −15.665 dB, reflecting weaker and more variable returns caused by direct exposure of the cable structure to sediments and hydrodynamic forces. The consistent differences between the two cable types demonstrate that each structure exhibits a distinctive acoustic signature that can be used as a discriminating parameter for mapping. This study provides important empirical evidence by presenting direct acoustic backscatter characterization of submarine cables in Indonesia and demonstrates that commercial echosounders can reliably support infrastructure inspection in shallow-water environments.